2018
DOI: 10.3390/su10093197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Quality of Returned-Used Products on the Optimal Design of a Manufacturing/Remanufacturing System under Carbon Emissions Constraints

Abstract: Due to environmental legislation pressure and the competition between manufacturing firms, a high number of production firms are obliged to collect and remanufacture used products. As a result, firm leaders and academic researchers are devoted to developing and managing new sustainable supply chains. Most of the published works in the literature assume that new and remanufactured products are of the same quality, and that all of the returned-used products are remanufacturable. However, in practice, new product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Political and sustainability agreements are increasingly in place to prevent major negative consequences from the human economic impact and weather effects. Sustainability is the limits imposed by technology and social organizations on the ability of the environment to meet current and future capabilities [8,9]. Zsyman et al [10] pointed out that green development is now the core theme in international climate change negotiations.…”
Section: Sustainable Development and Closed-loop Supply Chain Managementmentioning
confidence: 99%
“…Political and sustainability agreements are increasingly in place to prevent major negative consequences from the human economic impact and weather effects. Sustainability is the limits imposed by technology and social organizations on the ability of the environment to meet current and future capabilities [8,9]. Zsyman et al [10] pointed out that green development is now the core theme in international climate change negotiations.…”
Section: Sustainable Development and Closed-loop Supply Chain Managementmentioning
confidence: 99%
“…The first related area of literature is on the coopetition relationship in closed-loop supply chains. For example, Turki and Rezg [10] provided an optimal design for a manufacturing/remanufacturing system that differentiates between new and remanufactured products and sorts the used products into three quality levels and determined the optimal storage capacities and production decisions regarding new and remanufactured products while considering carbon emissions. Li et al [22] examine the influences of vertical and horizontal cooperation models on the optimal decisions and performance of a low-carbon closed-loop supply chain with a manufacturer and two retailers and found that the completely centralized model was best in all optimal decision results among all models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, practitioners with expertise in decision-making methodologies can also use preference ranking organization method for enrichment evaluation (PROMETHEE) [65,66], system dynamics [67,68], or optimization methods [69,70] to make the final decision.…”
Section: Decision-makingmentioning
confidence: 99%